Emigration and democracy - Frederic Docquier; Elisabetta Lodigiani; Hillel Rapoport; Maurice Schiff (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2011)
Migration is an important and yet neglected determinant of institutions. The paper documents the channels through which emigration affects home country institutions and considers dynamic-panel regressions for a large sample of developing countries. We find that emigration and human capital both increase democracy and economic freedom. This implies that unskilled (skilled) emigration has a positive (ambiguous) impact on institutional quality. Simulations show an impact of skilled emigration that is generally positive, significant for a few countries in the short run and for many countries in the long run once incentive effects of emigration on human capital formation are accounted for.
Keywords: O1; F22; 330; Migration; institutions; democracy; diaspora effects; brain drain